The relationship between pericoronitis and the positioning of impacted mandibular third molars - Bhikha, Vishal (My University, 2020)
Introduction: Impacted mandibular third molars may lead to a variety of conditions. Pericoronitis is an inflammatory condition of the gingival soft tissue surrounding the impacted or partially erupted tooth (mandibular third molar). Pericoronitis may result in varied pain, swelling, halitosis, abscess formation. Angulation and position of the mandibular third molar may be a contributing factor towards the development of pericoronitis. Aim: To investigate the relationship between pericoronitis and the positioning of impacted mandibular third molars.Methodology: This study is a retrospective study based on the records (clinical records and panoramic radiographs) of 201 patients who presented for surgical extraction of symptomatic impacted mandibular third molars diagnosed with pericoronitis. Data collection was done using a designed questionnaire. The Pell and Gregory, and Winter’s classifications were used to assess position and angulation respectively. Results: Pericoronitis was seen mostly in female patients (53.2%). The most predominant mandibular third molar angulation associated with pericoronitis was vertical (51.7%), followed by mesioangular (43.2%) and horizontal (3%). The most predominant position was IA (36.3%), followed by IIB (28.8%) and thirdly was IB (15.9%). The most common combination was a IA position with vertical angulation (36%). There was a statistically significant association observed between combination of classifications and pericoronitis (P= 0.01*).Conclusion: Pericoronitis is a condition that may be seen mostly between the ages of 20-29 years, affecting predominantly females. Pericoronitis occurrence is highly associated with vertically angulated mandibular third molars and/or mostly present in positions of class I/II ramus relation and class A depth. Patients presenting with unfavourable angulations, positions and patterns of mandibular third molars should be aware of the possibility of developing a pericoronal infection and symptoms thereof. It is advisable to consider some form of assistance or treatment modality.
A research report submitted in fulfilment of the requirements for the degree of Master of Science in Dentistry to the Faculty of Health Sciences, School of Oral Health Sciences, University of Witwatersrand, Johannesburg, 2020